Hydrogel Patterns in Microfluidic Devices by Do-It-Yourself UV-Photolithography Suitable for Very Large-Scale Integration - Anthony Beck; Franziska Obst; Mathias Busek; Stefan Grünzner; Philipp J. Mehner; Georgi Paschew; Dietmar Appelhans; Brigitte Voit; Andreas Richter (Micromachines, 2020)
The interest in large-scale integrated (LSI) microfluidic systems that perform high-throughput biological and chemical laboratory investigations on a single chip is steadily growing. Such highly integrated Labs-on-a-Chip (LoC) provide fast analysis, high functionality, outstanding reproducibility at low cost per sample, and small demand of reagents. One LoC platform technology capable of LSI relies on specific intrinsically active polymers, the so-called stimuli-responsive hydrogels. Analogous to microelectronics, the active components of the chips can be realized by photolithographic micro-patterning of functional layers. The miniaturization potential and the integration degree of the microfluidic circuits depend on the capability of the photolithographic process to pattern hydrogel layers with high resolution, and they typically require expensive cleanroom equipment. Here, we propose, compare, and discuss a cost-efficient do-it-yourself (DIY) photolithographic set-up suitable to micro-pattern hydrogel-layers with a resolution as needed for very large-scale integrated (VLSI) microfluidics. The achievable structure dimensions are in the lower micrometer scale, down to a feature size of 20 µm with aspect ratios of 1:5 and maximum integration densities of 20,000 hydrogel patterns per cm². Furthermore, we demonstrate the effects of miniaturization on the efficiency of a hydrogel-based microreactor system by increasing the surface area to volume (SA:V) ratio of integrated bioactive hydrogels. We then determine and discuss a correlation between ultraviolet (UV) exposure time, cross-linking density of polymers, and the degree of immobilization of bioactive components.